(untitled) (Pesquisa Odontológica Brasileira, 2002)
The determination of bacterial susceptibility to intracanal medicaments is a necessity. Nevertheless, few studies utilize the proper methodology to carry out that evaluation with anaerobes. In this study, the steps of a broth dilution method, carried out in microplates (microdilution) and tubes (macrodilution), to test the effect of traditional intracanal medicaments on anaerobic bacteria are described. The results are presented as values of minimal inhibitory and bactericidal concentrations (MIC and MBC). Standardized inocula of the anaerobic bacteria Prevotella nigrescens (ATCC 33563), Fusobacterium nucleatum (ATCC 25586) and Clostridium perfringens (ATCC 13124), in reinforced Clostridium medium (RCM) and supplemented Brucella broth, were submitted to different concentrations of calcium hydroxide, chlorhexidine digluconate, camphorated paramonochlorophenol and formocresol solutions. The drugs were diluted in the same culture broths, in microplates and tubes, and were then incubated in anaerobiosis jars at 37ºC for 48 or 96 hours. The determination of MICs was carried out through visual and spectrophotometric readings, and the determination of MBCs, through the plating of aliquots on RCM-blood agar. For that kind of study, the macromethod with spectrophotometric reading should be the natural choice. MICs and MBCs obtained with the macromethod were compatible with the known clinical performance of the studied medications, and the values varied according to the bacteria and culture media employed. RCM was the most effective medium and C. perfringens, the most resistant microorganism.